Transformation of the Institution of Administrative Complaints in Civilian Uniforms - Vadim Radaev (Journal of Economic Sociology, 2021)
Dear colleagues,On the day when this issue of our journal will be published, the students of the HSE University are expected to return from distant studies to their classes. We believe that this return is for good despite the obvious fact that the pandemic is still with us.